(untitled) (Journal of Islamic Law, 2025)
This article analyses the fatwa issued by the Majelis Ulama Indonesia (MUI, the Indonesian Council of Ulama) on the Ahmadiyah sect through the frameworks of Teun A. van Dijk’s critical discourse analysis. Addressing a research gap on language as an instrument of power in religious discourse, this study examines the graphic structure, syntax, semantics, lexical choices, and rhetorical strategies to reveal how the fatwa not only serves as a legal guideline within Islamic jurisprudence but also functions as an ideological tool reinforcing MUI’s authority within Indonesia’s religious hierarchy. Findings indicate that passive constructions, abstraction, generalisation, hyperbole, and repetition are employed to obscure agency, amplify societal demands, and frame the Ahmadis as a threat to social stability and Islamic orthodoxy. Lexical choices, such as “deviant”, “apostate”, and “misleading”, legitimise the marginalisation of Ahmadiyah followers and reinforce the binary opposition between mainstream Muslims and the outgroup. Additionally, rhetorical strategies within the fatwa shape public perception, strengthen MUI’s authority, and potentially foster institutional discrimination. This study demonstrates that religious discourse extends beyond doctrinal guidance, functioning as a mechanism of social control that sustains exclusionary practices within the religious sphere, thereby contributing to the broader discourse on language, ideology, and power in Islamic studies in Indonesia. [Artikel ini menganalisis Fatwa Majelis Ulama Indonesia (MUI) tentang Aliran Ahmadiyah dengan menggunakan pendekatan analisis wacana kritis yang dikembangkan oleh Teun A. van Dijk. Studi ini menyoroti kesenjangan penelitian terkait peran bahasa sebagai instrumen kekuasaan dalam wacana keagamaan, khususnya dalam membentuk kognisi sosial, konstruksi ideologis, dan dominasi institusional. Dengan menelaah struktur grafis, sintaksis, semantik, leksikal, dan retoris, penelitian ini mengungkap bahwa fatwa tersebut tidak hanya berfungsi sebagai pedoman hukum Islam, tetapi juga sebagai alat ideologis yang memperkuat posisi MUI dalam hierarki keagamaan Indonesia. Temuan menunjukkan bahwa strategi linguistik, seperti kalimat pasif, abstraksi, generalisasi, hiperbola, dan repetisi, digunakan untuk menyamarkan aktor, memperbesar tuntutan masyarakat, serta membingkai Ahmadiyah sebagai ancaman terhadap stabilitas sosial dan kemurnian Islam. Pilihan leksikal, termasuk istilah “sesat”, “murtad”, dan “menyesatkan”, berperan dalam melegitimasi marginalisasi terhadap pengikut Ahmadiyah serta memperkuat oposisi biner antara Muslim arus utama dan kelompok luar. Selain itu, strategi retoris dalam fatwa ini membentuk persepsi publik, meningkatkan otoritas MUI, serta berpotensi mendorong diskriminasi institusional. Studi ini menunjukkan bahwa wacana keagamaan tidak hanya merefleksikan norma Islam, tetapi juga berfungsi sebagai alat kontrol sosial yang mempertahankan praktik eksklusi dalam ranah keagamaan. Dengan demikian, penelitian ini berkontribusi pada kajian bahasa, ideologi, dan kekuasaan dalam wacana Islam di Indonesia.]